Altered cortical thickness associated with psychotic symptoms and cognitive profiles in involuntarily hospitalized, first-episode, drug-naive patients with schizophrenia - Tang, Ruru; Zhang, Wei; Fang, Xinyu; Shen, Xuran; Zuo, Bin; Ni, Longyan; Yan, Wei; Zhang, Rongrong; Xie, Shiping (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to explore the cognitive impairment characteristics, psychotic symptoms, and the relationship with alterations in cortical thickness in involuntarily hospitalized, first-episode, drug-naive schizophrenia patients.MethodsA total of 59 involuntarily hospitalized patients and 60 healthy controls were included. The MATRICS Consensus Cognitive Battery (MCCB) scale was used to evaluate cognitive function in involuntarily hospitalized patients and healthy controls. The Positive and Negative Syndrome Scale (PANSS) was utilized to evaluate psychotic symptoms in involuntarily hospitalized patients. Structural MRI scans were obtained from all participants, and the Desikan-Killiany template was used in FreeSurfer software to extract the cortical thickness values.ResultsInvoluntarily hospitalized patients exhibited cognitive impairments across seven cognitive domains compared to healthy controls. Additionally, these patients exhibited increased cortical thickness in the right temporal pole, left posterior cingulate gyrus, and left temporal pole compared to controls. Partial correlation analysis revealed that in the involuntarily hospitalized patients, the left posterior cingulate gyrus had a negative correlation with general symptoms, while the right temporal pole showed a positive correlation with negative symptoms. No correlation was found between cortical thickness and cognitive function in patients with involuntary hospitalization. In contrast, within the healthy control group, both the left and right temporal poles exhibited positive correlations with reasoning and problem-solving abilities.ConclusionsOur study reveals significant cognitive impairments and cortical thickness alterations in first-episode, drug-naive schizophrenia patients during their initial involuntary hospitalization. These cortical thickness alterations were significantly associated with psychotic symptoms, but not cognitive impairment. These findings suggest that cognitive dysfunction and symptom presentation in early-stage schizophrenia patients with involuntary hospitalization may be influenced by distinct neuroanatomical mechanisms.